CMT wire-arc additive manufacturing of 310 austenitic stainless steel: Microstructure-properties relationships - Ali Rahimi; Morteza Yazdizadeh; Masoud Vatan Ara; Majid Pouranvari (Journal of Materials Research and Technology)
This study examines the microstructure and mechanical properties of 310 austenitic stainless steel produced using cold metal transfer (CMT) wire arc additive manufacturing (WAAM). The microstructure of the WAAM-fabricated wall is characterized by epitaxial growth, elongated columnar grains that extend several millimeters in length, and a dendritic sub-solidification structure featuring elongated eutectic δ-ferrite along the interdendritic and grain boundaries. This microstructure contrasts with the annealed hot-rolled AISI 310, which exhibits a δ-ferrite-free, fully austenitic microstructure with fine equiaxed grains. The geometry of the dendrites, including primary and secondary dendrite arm spacing, is influenced by variations in cooling rates both along the building direction and within each deposited layer, as well as by remelting phenomena occurring in the interlayer boundary zone. The tensile behavior and Charpy V-notch impact performance of the additively manufactured part are compared to those of its wrought hot-rolled counterpart. The tensile strength, ductility, and energy absorption during impact tests are affected by the anisotropic microstructure of the manufactured part. The orientation of coarse columnar grains and the alignment of δ-ferrite along the interdendritic and grain boundaries are critical factors influencing the anisotropic tensile properties of the WAAM-fabricated SS310 austenitic stainless steel.